Inner Intrinsically Safe Criterion and Design Considerations of Buck Converter Based on Equivalent Inductance. Issue 3 (7th February 2019) - Liu, Shulin; Wu, Hao; Wang, Chaoying; Nie, Shen; Qi, Lili
Abstract: To obtain the intrinsic safety criterion of the Inner-intrinsic-Safety-Buck-Converter (ISBC) based on equivalent-inductance to guide its optimal design, the Inductor Disconnected Discharge (IDD) behavior of ISBC is researched, and the Equivalent-Simple-Inductive-Circuit (ESIC) based on the equivalent inductance is defined. According to ESIC based on the equivalent-current and the energy equivalence, the expression of the equivalent inductance L ei is derived. The effect of the inductance L, the capacitance C, the input voltage V i and the load resistance R L on L ei is deeply studied, and it's pointed out that L ei increases with the increase of V i, L, C, and R L, respectively. According to the minimal ignition current curve of the Simple-Inductive-Circuit (SIC), the nonexplosive intrinsically safe criterion based on L ei is proposed. Combining the proposed criterion, the output ripple voltage and the expression of L ei, the design region of the capacitance and inductance of the Buck converter meeting the demands of both inner intrinsic safety and electric performance is obtained. The feasibility of the design method and the proposed criterion is proved by the simulation and experimental results.